Post-Grouting Experiences for Reducing Groundwater Inflow at 500 m Depth of the Mizunami Underground Research Laboratory, Japan. (2017) - Tsuji, M.; Kobayashi, S.; Mikake, S.; Sato, T.; Matsui, H.
Abstract: This paper shows the application of two post-grouting works to a gallery at 500 m depth of Mizunami Underground Research Laboratory (MIU) in Japan. The ground water pressure was around 3.5 MPa during the campaign. A maximum grouting pressure was set at 5.0 MPa for the first post-grouting and 5.5 MPa for the second. Three new grouting concepts were applied to the post-grouting works; a new grout material, a new injection system, and a new post-grouting zone. As for a grout material, " durable liquid-type colloidal silica grout (CSG) " was applied to seal the narrow fractures. As for an injection system, "complex dynamic grouting method" was applied to improve the penetrability of the grout material. As for a post-grouting zone, "outside of the pre-grouted zone" was targeted to reduce the risk of erosion and leakage of fresh grout. The first post-grouting work in 2014 was designed by the new concepts combined with the ordinary ones for the comparative study. The reduction of the sectional inflow indicated that the hydraulic conductivity of the post-grouted rock mass to be lower than 10 -9 m/s by the back calculation. The second campaign in 2016 was designed by totally latest concepts. As a result, it was measured that all the dripping spots be lower than 1 l/min, which satisfied the severe criterion to perform the post-grouting for a deep repository in Sweden. The grouting works were successful in reducing the abundant water inflow from the rock mass with many fractures. It can be concluded that the developed grouting methodology in MIU is applicable for constructing the watertight tunnels in hard rock with lots of fractures and for the future disposal sites with a severe inflow requirement.